MARKET PROFITS ON THE OPERATING STATEMENT. - Schlatter, Chas. F. (The Accounting Review, 1942)
Abstract It is interesting to speculate on the extent to which a too strict adherence by accountants to well-established, conventional forms and methods, may lead to the introduction of new and questionable practices by business men. Accounting principles do not change, but the problems of business do. Old forms and old methods of accounting which once satisfactorily reflected the truth and were correct applications of principles, may, because of a change in business practice resulting from economic shifts and other causes, no longer reflect, or make full disclosure of, the truth. There are times when the correct application of principles may be defeated by slavish adherence to a standardized form. Perhaps the reluctance of the accountant to adapt the profit and loss statement to the financial and managerial needs for truth in some businesses is partially responsible for the introduction of the "last-in-first-out" method of pricing materials into process and of pricing goods sold. It is not the inventories, but rather the material taken from raw material store, the material taken from process as goods are finished, or the material included in the product taken from the finished goods inventory and sold, or all three, that are priced by this method.